lim x->0 [(1+tanx)^1⼀2-(1+sinx)^1⼀2]⼀[xln(1+x)-x^2]

2025-02-23 22:41:04
推荐回答(1个)
回答1:

上下都乘以(1+tanx)^1/2-(1+sinx)^1/2则,
分子变为(1+tanx)-(1+sinx)=tanx-sinx

分母变为[xln(1+x)-x^2]*[(1+tanx)^1/2+(1+sinx)^1/2]

原式=LIM【(tanx-sinx)/{[xln(1+x)-x^2]*[(1+tanx)^1/2+(1+sinx)^1/2]}

=LIM【(tanx-sinx)/[x(ln(1+x)-x)]】*LIM【1/[(1+tanx)^1/2+(1+sinx)^1/2]}】

(由函数的连续性,后一项的极限是1/2)
下面求
LIM【(tanx-sinx)/[x(ln(1+x)-x)]】
由于
tanx-sinx=sinx/cosx-sinx*cosx/cosx=sinx(1-cosx)/cosx
所以
LIM【(tanx-sinx)/[x(ln(1+x)-x)]】=LIM【sinx(1-cosx)/[x(ln(1+x)-x)]/cosx】

=LIM【x^3/(2x(ln(1+x)-x))*1/cosx】(根据等价无穷小)
=LIM【x^2/(ln(1+x)-x)】*LIM(1/cosx)(显然后一项极限是1)
=LIM【2x/[1/(1+x)-1]】(洛比达法则)
=-1

所以原式=-1/2